The Kaiser's army the politics of military technology in Germany during the machine age, 1870-1918 - Brose, Eric Dorn, 1948- (Oxford University Press, 2001)
This volume covers a fascinating period in the history of the German army, a time in which machine guns, airplanes, and weapons of mass destruction were first developed and used. Eric Brose traces the industrial development of machinery and its application to infantry, cavalry, and artillery tactics.